2020
DOI: 10.26803/ijlter.19.9.19
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Writing Module on Enhancing the Writing Skills of Omani General Foundation Program Students

Abstract: This study aimed to investigate the effectiveness of a developed writing module on enhancing the General Foundation Program students’ writing skills. The study made use of a pre-test and post-test quasi-experimental design. The study participants incorporated 70 Omani students and 2 EFL teachers. The students were divided into experimental and control groups. The experimental group incorporated 35 students who studied English at the General Foundation Program of Sur Nursing Institute. The control group involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Writing is a way of sharing personal meaning and writing courses emphasize the power of the individual to construct his or her views on a topic. It is a multi-aspect communicative skill and teaching writing can be ideally thought of as a certain dynamic process, developing students' skills in spelling, grammar, punctuation, vocabulary use, composition, and style (Abdelmohsen et al, 2020;Terenin, 2015) Plenty of previous study has shown that writing English paragraph is not easy for EFL students. A common problem found in composing paragraph writing is students are not aware to identify part of the paragraph, identify different types of paragraphs, and are not able to use cohesive devices correctly (Elazeez, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Writing is a way of sharing personal meaning and writing courses emphasize the power of the individual to construct his or her views on a topic. It is a multi-aspect communicative skill and teaching writing can be ideally thought of as a certain dynamic process, developing students' skills in spelling, grammar, punctuation, vocabulary use, composition, and style (Abdelmohsen et al, 2020;Terenin, 2015) Plenty of previous study has shown that writing English paragraph is not easy for EFL students. A common problem found in composing paragraph writing is students are not aware to identify part of the paragraph, identify different types of paragraphs, and are not able to use cohesive devices correctly (Elazeez, 2019).…”
Section: Introductionmentioning
confidence: 99%